2021
DOI: 10.1002/eat.23502
|View full text |Cite
|
Sign up to set email alerts
|

Within‐subject weight variability in bulimia nervosa: Correlates and consequences

Abstract: Objective The oscillations between binge eating, purging, and dieting in bulimia nervosa (BN) may produce substantial within‐subject weight variability. Although weight variability has been predictive of eating‐ and weight‐related variables in community samples, it has not been empirically examined in eating disorders. The current study examined cross‐sectional and prospective associations between weight variability and BN pathology. Method Four weights were collected over an average of 42.02 days, and weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…It is notable that weight variability was not associated with any treatment outcome when simultaneously accounting for average daily weight gain, especially as recent research highlighted the predictive value of weight variability on core eating disorder pathology in individuals with bulimia nervosa (Chen et al, 2021). This is also in contrast to Hartmann et al (2007), where weight variability was associated with treatment failure.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is notable that weight variability was not associated with any treatment outcome when simultaneously accounting for average daily weight gain, especially as recent research highlighted the predictive value of weight variability on core eating disorder pathology in individuals with bulimia nervosa (Chen et al, 2021). This is also in contrast to Hartmann et al (2007), where weight variability was associated with treatment failure.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Hartmann et al (2007) found a statistically significant negative association of within-person weight variability during week 3-4 of inpatient treatment on treatment success at discharge. Recently, a similar analysis in a treatment-seeking sample of individuals with bulimia nervosa found significant associations of within-person weight variability with core eating disorder psychopathology at 6-months follow-up (Chen et al, 2021). Yet, it is unknown whether similar associations of weight variability with core eating disorder pathology can be found in AN.…”
Section: Effects Of Weight Variability On Treatment Outcomementioning
confidence: 88%
See 1 more Smart Citation
“…This might have reduced variance in weight variability in our sample compared to individuals with bulimia nervosa. Second, Chen et al (2021) used a slightly different level-1 model that included fixed effect estimates for weight change, and only included BMI and weight variability into their level-2 analyses, but not linear weight gain. Thus, their weight variability estimate might be confounded by weight gain for patients that increased weight during the study.…”
Section: Discussionmentioning
confidence: 99%
“…(2007) found a statistically significant negative association of within‐person weight variability during week 3–4 of inpatient treatment on treatment success at discharge. Recently, a similar analysis in a treatment‐seeking sample of individuals with bulimia nervosa found significant associations of within‐person weight variability with core ED psychopathology at 6‐month follow‐up (Chen et al., 2021). Yet, it is unknown whether similar associations of weight variability with core ED pathology can be found in AN.…”
Section: Introductionmentioning
confidence: 88%